2022
DOI: 10.5539/jsd.v15n5p73
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholder Perception and Institutional Approach to Rooftop Gardening (RTG) of Urban Areas in Dhaka, Bangladesh

Abstract: Dhaka is one of the world's most populated cities and lacks the open fields and greeneries required for healthy living. Whereas urban sustainability depends on the greenness of the environment and the reduction of food dependency on the rural supply, currently, the city is failing to meet both requirements. The aim of this research is to understand why rooftop gardening (RTG) has failed to find its place in the policy agenda of Bangladesh, despite having support from citizens and experts. In answering … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…21-22). However, previous studies (Shariful Islam, 2002;Asad et al, 2014;Safayet et al, 2017, Islam et al, 2019Shahidullah et al, 2022) focused more on the current practices, potentiality, perceptions, institutional settings, barriers as well as future prospects of RTG in Dhaka. Moreover, studies identified that RTG could be an alternative strategy for promoting food security in Dhaka (Chowdhury et al, 2020), and a source of environment conservation (Islam et al, 2020).…”
Section: Review Of Literaturementioning
confidence: 99%
“…21-22). However, previous studies (Shariful Islam, 2002;Asad et al, 2014;Safayet et al, 2017, Islam et al, 2019Shahidullah et al, 2022) focused more on the current practices, potentiality, perceptions, institutional settings, barriers as well as future prospects of RTG in Dhaka. Moreover, studies identified that RTG could be an alternative strategy for promoting food security in Dhaka (Chowdhury et al, 2020), and a source of environment conservation (Islam et al, 2020).…”
Section: Review Of Literaturementioning
confidence: 99%